Effects of Oral Maternal Administration of Caffeine on Reproductive Functions of Male Offspring of Wistar Rats (Nigerian Journal of Physiological Sciences, 2021)
Summary: Caffeine was investigated for its possible fetal programming effects on reproductive function of male offspring. Sixty-five pregnant Wistar rats were grouped into four. Group 1 was control and received distilled water. Groups 2, 3 and 4 were treated orally with 1.14, 3.42 and 5.70 mg/kg body weight of caffeine respectively. Each group was subdivided into four based on gestation days (GD) 1-7, 8-14, 15-21 and 1-21. The day of parturition was taken as postnatal day zero (0). Male offspring were sacrificed on postnatal day 70. Parameters determined were: weight at birth, body weight at postnatal day 21 and 70, anogenital distance (AGD) index, sperm parameters, reproductive organ weight, histology and hormonal profile (testosterone, FSH and LH). Data were analyzed using Analysis of Variance. Level of significance was taken at P